A policy analysis to promote conservation and use of small millet underutilized species in India. Issue 4 (4th July 2017) - Notaro, Veronica; Padulosi, Stefano; Galluzzi, Gea; King, Israel Oliver
ABSTRACT: Despite the important role of Neglected and Underutilized Species (NUS) in diversifying agriculture, supporting traditional farming systems and improving food and nutritional security particularly in marginal lands, very little attention is being paid to their mainstreaming in national policies and institutions. Based on a detailed review of the regulatory frameworks governing the conservation, sustainable use and equitable sharing of benefits arising out of plant genetic resources and the circulation and registration of seeds and improved varieties, this paper discusses the extent to which the measures in place in India may favour or affect the conservation and use of NUS. In addition to these frameworks, in view of the major change realized by the 2013 National Food Security Act which has included coarse cereals in the country's Public Distribution System (PDS), the paper also incorporates this latest policy in its analyses. A special focus is given to small millets, a group of species with unexploited economic and nutritional potential but extremely important for marginal communities' food security and livelihoods. A set of policy recommendations and opportunities to explore are proposed to address the identified constraints with the purpose of creating a more supportive policy environment and enhancing the national capacity to promote NUS.